Faktor Risiko Distal yang Memengaruhi Anemia pada Anak Usia 6-59 Bulan: Analisis Data Demographic and Health Survey Zimbabwe 2015 - Ariza, Nahya Rahmatul; Mahmudiono, Trias; Mahmudah; Melaniani, Soenartalina (Media Gizi Kesmas, 2024)
Background: Anemia is the cause of child death in Africa. More than one-third (37%) of children aged 6-59 months in Zimbabwe are anemic. Anemia is caused by two factors, namely proximal factor (attached to the individual) and distal factor (not attached to the individual). Objectives: This study aims to determine the distal risk factors associated with anemia in children aged 6-59 months in Zimbabwe. Methods: A cross-sectional study design by analyzing Demographic and Health Survey (DHS) data for Zimbabwe in 2015. The total sample was 4303 households with children aged 6-59 months and fulfilled all the study variables. That became independent variables in this study were land ownership, types of livestock, and two factors from the results of the Principal Component Analysis test, water and toilet sanitation and building sanitation. Univariate analysis was performed to see the frequency distribution of each variable, then bivariate analysis with chi-square and Mann-Whitney tests to determine factors that were significantly related to the incidence of anemia and further tested with logistic regression. Results: Based on the results of this study, it was found that variables that were significantly related to the incidence of anemia were age, agricultural land ownership, types of livestock, water and toilet sanitation, and building sanitation. From several variables that became distal risk factors, it was found that variables that increased the risk factors for anemia in children aged 6-59 months, namely not having agricultural land (OR=2.84; 95% CI=2.38-3.4; p<0, 05), do not own livestock (OR=1.72; 95%CI=1.48-2; p<0.05) own poultry (OR=1.45; 95%CI=1.2-1.74) ; p<0.05) and building sanitation (OR=1.07; 95% CI=1-1.14; p<0.05). In addition, this study found a protective factor against the incidence of anemia in children aged 6-59 months in Zimbabwe, namely water and toilet sanitation (OR=0.85; 95% CI=0.8-0.91; p<0.05). Conclusions: The causes of anemia in children aged 6-59 months are multifactorial. We suggest that policymakers plan an integrated program specifically in agriculture and animal husbandry so that every household has agricultural land and livestock to reduce the incidence of anemia in children aged 6-59 months in Zimbabwe.